Peroneal Arteriovenous Fistula and Pseudoaneurysm: An Unusual Presentation - Ching, Kevin C. (Hindawi Publishing Corporation, 2014)
Peroneal artery arteriovenous fistulas and pseudoaneurysms are extremely rare with the majority of reported cases due to penetrating, orthopedic, or iatrogenic trauma. Failure to diagnose this unusual vascular pathology may lead to massive hemorrhage or limb threatening ischemia. We report an interesting case of a 14-year-old male who presented with acute musculoskeletal pain of his lower extremity. Initial radiographs were negative. Further imaging workup revealed a peroneal arteriovenous fistula with a large pseudoaneurysm. After initial endovascular intervention was unsuccessful, the vessels were surgically ligated in the operating room. Pathology revealed papillary endothelial hyperplasia consistent with an aneurysm and later genetic testing was consistent with Ehlers-Danlos syndrome Type IV. This case illustrates an unusual cause of acute atraumatic musculoskeletal pain and uncommon presentation of Ehlers-Danlos syndrome.